2002
DOI: 10.1001/archsurg.137.8.908
|View full text |Cite
|
Sign up to set email alerts
|

Early and Late Recipient Graft Function and Donor Outcome After Laparoscopic vs Open Adult Live Donor Nephrectomy for Pediatric Renal Transplantation

Abstract: Background: Laparoscopically procured live donor kidney grafts are increasingly transplanted into pediatric recipients. The safety and efficacy of this changed surgical practice are unknown. Hypothesis: Outcomes of laparoscopic vs open donor grafts in recipients 18 years and younger are equivalent. Design and Setting: Retrospective review at an academic tertiary care referral center. Patients: Eleven consecutive pediatric recipients of laparoscopically procured kidneys between April 1, 1997, and December 31, 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
40
2
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 36 publications
4
40
2
1
Order By: Relevance
“…These findings are consistent with the previously discussed single center studies that had reported higher early post-transplant serum creatinine levels in laparoscopic kidney graft recipients (10,13,14). Our findings are in line with, and explained by, experimental observations that pneumoperitoneum decreases cortical renal blood flow, renal vein flow and creatinine clearance, and causes oliguria (15)(16)(17).…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…These findings are consistent with the previously discussed single center studies that had reported higher early post-transplant serum creatinine levels in laparoscopic kidney graft recipients (10,13,14). Our findings are in line with, and explained by, experimental observations that pneumoperitoneum decreases cortical renal blood flow, renal vein flow and creatinine clearance, and causes oliguria (15)(16)(17).…”
Section: Discussionsupporting
confidence: 93%
“…Ratner noted similar significant differences on postoperative days 2 and 3 (13). In one of our previous studies, we found significantly higher creatinine levels in pediatric laparoscopic kidney recipients on day 1 and day 4 (14). Moreover, several additional studies have documented a trend towards higher early post-transplant creatinine levels for laparoscopic graft recipients, albeit not at a statistically significant level (11,19,20).…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations